Kesiapan Tenaga Kerja Indonesia Sektor Perhotelan dalam Menghadapi Implementasi MEA - Tiffany Fortunatan; Hallie Josias Sahertian (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2015)
At the end of 2015, Indonesia along with other countries which is incorporated in ASEAN organization will implement the ASEAN Economic Society (AEC). One of the sectors that is included in the first stage of implementation is the tourism and hospitality sector. Data stated that the opportunity of AEC imple-mentation for Indonesia can help fasten economic growth in a larger scale of market. But, there are also challenges need to be faced so that Indonesian labors can compete with the labors from other country. One of the important strategies is to adjust standardization and give certification of competence for all of tourism and hospitality labors in Indonesia.